COMPARATIVE STUDY OF TENSION BAND WIRING, MODIFIED TENSION BAND WIRING AND FULLY THREADED CANNULATED CANCELLOUS SCREWS FOR FIXATION OF MEDIAL MALLEOLUS FRACTURES - SANTOSH S BORKAR; SHIVRAJ S KONDE; RAJIV MUNDE; SHANTANU PATIL; SHUBHAM CHAUDHARI; MANAS PUSALKAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: To compare the three most commonly used fixation techniques: “Tension band wiring, modified tension band wiring, and fully threaded cannulated cancellous screws for fixation of medial malleolus fractures.” Methods: A prospective comparative cohort study was carried out at a tertiary care hospital in rural Maharashtra. Patients were allocated into three groups, with 33 patients in each group. The internal fixation was done by tension band wiring, modified tension band wiring, or fully threaded cannulated cancellous screws, depending on the group to which a patient belonged. Patients were assessed using the Baird and Jackson scoring system at each follow-up at immediate post-operative period, at 3, 6, 12, 24 weeks, and 1 year. For statistical purposes, p<0.05 was considered statistically significant. Results: There was no significant difference in the three groups as regards age, body mass index, and mean time from injury to management. The most common mode of injury was road traffic accidents (51.52%), followed by falls from height (27.27%) and sports-related injuries (21.21%). The mean duration of surgery was significantly longer in cases managed by tension band wiring as compared to the other two groups. Implant-related complications were significantly less in the threaded cannulated cancellous screw group as compared to the other two groups. Overall excellent to good outcomes were observed in 97% of cases of cannulated cancellous screws as well as in modified tension band wiring and 84.8% of cases of tension band wiring, respectively. Conclusion: Fully threaded cannulated cancellous screws or modified tension band wiring should be used for the management of medial malleolar fractures while considering the functional outcome and complications associated with each and patient-related factors.